Привидение из Простоквашино: повесть-сказка / Э. Успенский ; художник А. Шевченко - Успенский Эдуард Николаевич (АСТ, 2007)
Экземпляры: ф.18 (20231122) / Инвентарный номер: 4729 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: У-77 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44